Reverse gastric tube oesophageal substitution for staged repair of oesophageal atresia and tracheo-oesophageal fistula - Christopher Olusanjo Bode; Adesoji Oludotun Ademuyiwa (Wolters Kluwer Medknow Publications, 2014)
The management of oesophageal atresia and tracheo-oesophageal atresia (OATOF) is very challenging. While in developed countries survival of patients with this condition has improved, the outcome in many developing countries has been poor. Primary repair through a thoracotomy (or video-assisted thoracoscopic surgery where available) is the gold standard treatment of OATOF. However, in our setting where patients typically present late and with minimum support resources such as Neonatal Intensive Care Unit and total parenteral nutrition; staged repair may be the only hope of survival of these patients and this communication highlights the essential steps of this mode of treatment.